Features of Geographical Profiling within Law Enforcement Agencies (Law and Safety, 2020)
The tools, organization and tactics of conducting geographical profiling of serial crimes have been analyzed. Theoretical basis for compiling geographical profiles has been outlined. Some elements of criminological theories of standard activity, rational choice and modeling of crimes have been briefly revealed. Types of spatial criminal behavior have been outlined. The author has presented an algorithm for determining the type of serial offender for the correct compilation of a geographical profile. The general algorithm of geographical profiling and the procedure of calculation of key distances have been outlined. The author has stated the need to take into account local factors for the correct compilation of the geographical profile; has analyzed the suitability of the application of geographical profiling for different categories of crimes. Some organizational and tactical techniques and methods of compiling geographical profiles have been revealed and several scientific approaches to such activities have been considered. Peculiarities of the application of thermal maps during the preparation of geographical profiles have been revealed. Empirical material on determining the distances from the witness marks to crime scenes for different types of offenses, as well as the impact of different socio-demographic factors on these distances. Some programming solutions for the implementation of geographical profiling tasks have been studied. The author has analyzed the possibility of applying geographical profiling methods to crimes that can be committed remotely (cybercrime, telephone fraud, etc.). The author has provided successful and unsuccessful examples, which reveal the approaches to the implementation of geographical profiling. The conditions and factors that must be taken into account while compiling profiles have been outlined. It has been concluded that it is necessary to strengthen the use of geographical profiling tools in Ukrainian law enforcement agencies. The author has outlined some measures that will contribute it.
Keywords: serial crimes; witness mark (point of reference); geographical profiling; methods; crime combating